Taxonomic sufficiency and effects of environmental and spatial drivers on aquatic insect community. (December 2019) - Godoy, B.S.; Faria, A.P.J.; Juen, L.; Sara, L.; Oliveira, L.G.
Graphical abstract: Highlights: The family level identification is effective in the bioassessment of aquatic insects. Megaloptera and Heteroptera are good surrogates of other orders of insects. Using spatial context improved the detection of environmental drivers. Water flow, pH and electrical conductivity influence the composition of the entire community. Abstract: Studies on aquatic insects have found divergent results when assessing the effects of the environment and spatial structure on the community. The inappropriate choice of taxonomic resolution or variables may be the determinant for such results. We tested whether identification to the family level is enough to approximate results obtained using genus in detecting environmental and spatial effects. We sampled the aquatic insect communities in 110 streams of the Brazilian Cerrado (vegetation type savanna). We used PROTEST analyses to determine the similarity of community configuration at the family and genus resolutions and the overlap of community structure among all pair of insect orders. We used a partial redundancy analysis (pRDA) to determine the effects of environmental and spatial factors, for the entire community and for each insect order individually. The community configurations using family and genus were congruent, as were one-third of orders. The family level reduced the unexplained portion of variance when compared with genus level. Water movement, chemical condition and habitat integrity were relevant for community structure. In addition, the use of family level is a good alternative for studies using aquatic insect communities in Cerrado streams.